ANALISIS BERPIKIR KREATIF GENERASI ALPHA DALAM MENYELESAIKAN WORD PROBLEM MATHEMATICS DITINJAU DARI GAYA BELAJAR SISWA SMP - Sukma Ayu; FX Didik Purwosetiyono; Dewi Wulandari (Journal of Mathematics Education and Science, 2026)
This study aims to investigate and analyze the creative thinking abilities of Generation Alpha junior high school students in solving systems of linear equations in two variables (SPLDV) word problems, viewed from their learning styles. The research employed a descriptive qualitative approach supported by NVivo software for automatic coding (autocode) and thematic visualization. The subjects consisted of 24 eighth-grade students from a school in Tegal regency, with results showing that 45.8% were visual learners, 29.1% auditory learners, and 25% kinesthetic learners. Furthermore, three students were purposively selected since it adequately represents the variety within the category to represent each learning style category for in-depth analysis. The instruments used included a learning style questionnaire, SPLDV word problem tests, and interview guidelines. Data were analyzed using the Miles and Huberman interactive model, while validity was ensured through methodological triangulation. The findings reveal that: (1) visual learners demonstrated all four indicators of creative thinking, with a notable strength in flexibility; (2) auditory learners achieved three indicators, particularly excelling in fluency; and (3) kinesthetic learners fulfilled four indicators, with a strong emphasis on elaboration. The prevalence of short-form visual content on social media influences Generation Alpha’s learning preferences, which are faster-paced and more visually oriented.